SYSTEMATIC LITERATURE REVIEW OF A SCIENTIFIC JOURNAL: IMPROVING LITERACY IN ONLINE CLASSROOM LEARNING - Eska Perdana Prasetya (University of Kuningan, 2021)
This research is a systematic literature review research that can provide a clear picture of what has been investigated and what gaps require further research, then aims to overcome this problem by identifying, critically evaluating, and integrating the findings of all studies, and aiming not to just to gather all the evidence on the research question; it is also intended to support the development of evidence-based guidelines for practitioners. This study uses ten main articles to find out how to improve literacy in online classrooms. This main article was taken because it is related to the main objective of this research, namely improving literacy in online classroom learning, which we all know that we are living in the era of the Covid 19 pandemic, which forces us to change all the order of life including in the world of education. The result of this research is that there are seven things that can improve literacy in online classroom. There are scientific literacy and literacy learning opportunities, digital tools and using technology, students' creativity and creating new applications, online environments and content knowledge, teachers and students hold positive attitudes, teaching philosophy and pedagogical knowledge, and texts and resource's positive identity work.